Signifikansi Masyarakat Kitab Bagi Dialog Antariman: Telaah Eksploratif atas Konsepsi Mohammed Arkoun - Baedhowi - (Millah: Journal of Religious Studies, 2004)
This paper tries to discuss Arkoun's thought regarding the genuine concept of Revelation. His concept begins to elaborate Revelation in the history of al-Qur'an and Muslim Tradition. From historical background of Ahl al-Kitab (People of the Book) has been founded the same task and tool in history of salvation (HP). Beginning from decisive issues of Ahl al-Kitab, Arkoun works out the concept of "The society of the Book". He uses a deconstruction method to find vocabulary, methods and intellectual attitudes relevant to the presentation of Revelation with: a. the requirement of modern historical analysis; b. the philosophical evaluation of the implicit or explicit postulates of teaching and; c. the benefit of modern rationality and scientific thought. From these views, the writer tries to elaborate the significances of Arkoun's thought as a basic need of dialogues and the development of discourses in multi-faiths and multi-religions societies.